The Influence of the Tourism Sector and GRDP on Poverty (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the influence of the tourism sector and GRDP on poverty in Central Java. This type of research is quantitative research, the data used in this study is secondary data obtained by the method of collecting library data from relevant agencies such as the Central Java Provincial Statistics Agency and the Youth, Sports, and Tourism Office of Central Java Province. The analytical tool used is panel data regression which combines time-series data (2015-2019) and cross-section (35 districts/cities in Central Java) with the best method, namely the Fixed Effect Model (FEM). The results of the analysis show that the variable number of tourists has a probability of 0.4497, the variable number of hotels has a probability of 0.0000 and the GRDP variable has a probability of 0.0000 against the percentage of the number of poor people. Based on the results of the study, it was concluded that the variable number of tourists had no effect on the variable percentage of the poor population and the variable number of hotels and GRDP had a negative effect on the percentage of the number of poor people. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh sektor pariwisata dan PDRB terhadap kemiskinan di Jawa Tengah. Jenis penelitian ini adalah penelitian kuantitatif, data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dengan metode pengumpulan data kepustakaan dari instansi terkait seperti Badan Pusat Statistik Provinsi Jawa Tengah dan Dinas Pemuda, Olahraga, dan Pariwisata Provinsi Jawa Tengah. Alat analisis yang digunakan adalah regresi data panel yang menggabungkan data time-series (2015-2019) dan cross section (35 kabupaten/kota di Jawa Tengah) dengan metode terbaik yaitu Fixed Effect Model (FEM). Hasil analisis menunjukkan bahwa variabel jumlah wisatawan memiliki probabilitas 0,4497, variabel jumlah hotel memiliki probabilitas 0,0000 dan variabel PDRB memiliki probabilitas 0,0000 terhadap persentase jumlah penduduk miskin. Berdasarkan hasil penelitian disimpulkan bahwa variabel jumlah wisatawan tidak berpengaruh terhadap variabel persentase penduduk miskin dan variabel jumlah hotel dan PDRB berpengaruh negatif terhadap persentase jumlah penduduk miskin.